Institutional Analysis of Tourism Destination Development in Karst Landscape Area: Community-based Tourism in Ngelanggeran Village - Andjanie, Isabella Fitria; Suhirman, Suhirman (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
The village of Nglanggeran in Gunungkidul possesses abundant natural and cultural tourism attractions. Through local wisdom and community-based tourism management, Nglanggeran has received numerous accolades as a Village Tourism destination. However, being part of the Karst Landscape Protection Area, Nglanggeran needs to consider a conservative and sustainable tourism development strategy that involves relevant stakeholders. This research aims to analyse the roles, positions, and interests of stakeholders within the community-based institution, which is the strength of Nglanggeran as a tourism village. The methodology combines literature study, content analysis, qualitative descriptive analysis, and Social Network Analysis using scientific articles and Regional Regulations (Perda) as data sources to map the institutional network patterns in Nglanggeran village. Aligning the institutional analysis results with the Perda containing tourism policy guidelines in the protected area, particularly the Karst Landscape Area in Nglanggeran village, yields recommendations to strengthen institutional functions in the effort to develop community-based and sustainable tourism in Nglanggeran village.